SOCIOEMOTIONAL WEALTH: ALTRUISME, RESIPROKAL, DAN TRUST DALAM MEM- BANGUN MASYARAKAT KRITIS BONUM COMMUNE - Herlina Yoka Roida (UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2020)
EJorts to democracy without thinking about the common interest are like a recipe for anger and deadlock, and everything starts from a critical attitude and heretical democratic rhetoric. Therefore, it is necessary to explore a participatory model that does not only begin and end with voting, but a system that involves trust and reciprocal altruistic behavior as a driving force for the critical attitude of society in realizing common interests. A system that educates people about hu- man behavior and how to collaborate in today’s sharing world. This system also needs to equip people with the ability to imagine well, so that in the end a critical attitude is directed to the ability to solve problems that involve long-term common interests based on community socio-emotional wealth, not only focusing on short- term gains.